login

Year-end appeal: Please make a donation to the OEIS Foundation to support ongoing development and maintenance of the OEIS. We are now in our 61st year, we have over 378,000 sequences, and we’ve reached 11,000 citations (which often say “discovered thanks to the OEIS”).

A213566
Rectangular array: (row n) = b**c, where b(h) = F(h), c(h) = (n-1+h)^2, F = A000045 (Fibonacci numbers), n>=1, h>=1, and ** = convolution.
4
1, 5, 4, 15, 13, 9, 36, 33, 25, 16, 76, 71, 59, 41, 25, 148, 140, 120, 93, 61, 36, 273, 260, 228, 183, 135, 85, 49, 485, 464, 412, 340, 260, 185, 113, 64, 839, 805, 721, 604, 476, 351, 243, 145, 81, 1424, 1369, 1233, 1044, 836, 636, 456, 309, 181, 100
OFFSET
1,2
COMMENTS
Principal diagonal: A213567.
Antidiagonal sums: A213570.
Row 1, (1,1,2,3,5,...)**(1,4,9,16,25,...): A053808.
Row 2, (1,1,2,3,5,...)**(4,9,16,25,...).
Row 3, (1,1,2,3,5,...)**(16,25,49,...).
For a guide to related arrays, see A213500.
LINKS
FORMULA
T(n,k) = 4*T(n,k-1)-5*T(n,k-2)+T(n,k-3)+2*T(n,k-4)-T(n,k-5).
G.f. for row n: f(x)/g(x), where f(x) = x*(n^2 - (2*n^2 - 2*n - 1)*x + (n - 1)^2 *x^2) and g(x) = (1 - x - x^2)*(1 - x )^3.
T(n,k) = n*(n*F(k+2) + 2*F(k+3)) + F(k+6) - (n+2)*(2*k+n+2) - k^2 - 4, F = A000045. - Ehren Metcalfe, Jul 10 2019
EXAMPLE
Northwest corner (the array is read by falling antidiagonals):
1....5....15....36....76
4....13...33....71....140
9....25...59....120...228
16...41...93....183...340
25...61...135...260...476
MATHEMATICA
(* First program *)
b[n_]:= Fibonacci[n]; c[n_]:= n^2;
t[n_, k_]:= Sum[b[k-i] c[n+i], {i, 0, k-1}]
TableForm[Table[t[n, k], {n, 1, 10}, {k, 1, 10}]]
Flatten[Table[t[n-k+1, k], {n, 12}, {k, n, 1, -1}]]
r[n_]:= Table[t[n, k], {k, 1, 60}] (* A213566 *)
d = Table[t[n, n], {n, 1, 40}] (* A213567 *)
s[n_]:= Sum[t[i, n+1-i], {i, 1, n}]
s1 = Table[s[n], {n, 1, 50}] (* A213570 *)
(* Second program *)
With[{F = Fibonacci}, Table[k*(k*F[n-k+3] +2*F[n-k+4]) + F[n-k+7] -(k+2) *(2*n-k+4) -(n-k+1)^2 -4, {n, 12}, {k, n}]//Flatten] (* G. C. Greubel, Jul 26 2019 *)
PROG
(PARI) f=fibonacci;
for(n=1, 12, for(k=1, n, print1(k*(k*f(n-k+3) +2*f(n-k+4)) + f(n-k+7) -(k+2)*(2*n-k+4) -(n-k+1)^2 -4, ", "))) \\ G. C. Greubel, Jul 26 2019
(Magma) F:=Fibonacci; [k*(k*F(n-k+3) +2*F(n-k+4)) + F(n-k+7) -(k+2)*(2*n-k+4) -(n-k+1)^2 -4: k in [1..n], n in [1..12]]; // G. C. Greubel, Jul 26 2019
(Sage) f=fibonacci; [[k*(k*f(n-k+3) +2*f(n-k+4)) + f(n-k+7) -(k+2)*(2*n-k+4) -(n-k+1)^2 -4 for k in (1..n)] for n in (1..12)] # G. C. Greubel, Jul 26 2019
(GAP) F:=Fibonacci;; Flat(List([1..12], n-> List([1..n], k-> k*(k*F(n-k+3) +2*F(n-k+4)) + F(n-k+7) -(k+2)*(2*n-k+4) -(n-k+1)^2 -4 ))); # G. C. Greubel, Jul 26 2019
CROSSREFS
Sequence in context: A154225 A188627 A203976 * A143129 A185731 A177765
KEYWORD
nonn,tabl,easy
AUTHOR
Clark Kimberling, Jun 19 2012
STATUS
approved